Combined application of inoculant, phosphorus and organic manure improves grain yield of cowpea - Ulzen, J.; Abaidoo, Robert C.; Ewusi-Mensah, N.; Masso, C. (Informa UK Limited, 2020)
Low concentrations of P and organic manure in savanna soils limit cowpea response to rhizobia. The study was conducted to determine the combined effect of P and organic manure on cowpea response to rhizobia in a factorial experiment arranged in randomized complete block design with three replications on smallholder farmers’ fields in northern Ghana in 2015. The factors were two levels of Bradyrhizobium inoculant, two levels of P fertilizer, three treatments of manure (fertisoil, cattle manure, and no manure). Addition of Bradyrhizobium inoculant to P and fertisoil significantly increased shoot biomass yield from 1677 kg ha−1 in the plots without Bradyrhizobium inoculation to 1913 kg ha−1. Likewise, the addition of Bradyrhizobium inoculant to P and cattle manure significantly increased shoot biomass from 1437 kg ha−1 to 1813 kg ha−1. Grain yield increases of 1427 and 1278 kg ha−1 were obtained over the control when either fertisoil or cattle manure and P, respectively, were added to Bradyrhizobium inoculant. The value cost ratio for adding Bradyrhizobium inoculant to phosphorus and fertisoil was two indicating that it could be attractive to risk-averse smallholder farmers. The study demonstrated the potential of the combined application of organic matter and P to improve cowpea response to Bradyrhizobium inoculation.